ELECTROCHEMISTRY STUDY ON THE RELATIONSHIP BETWEEN GRAIN BOUNDARY STATE AND CORROSION BEHAVIOR OF ULTRAFINE GRAINED IRON CHROMIUM ALLOY - Ahadi Damar Prasetya; Muhammad Rifai; Ahmad Hasan As'ari; Mujamilah Mujamilah; Hiroyuki Miyamoto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
ELECTROCHEMISTRY STUDY ON THE RELATIONSHIP BETWEEN GRAIN BOUNDARY STATE AND CORROSION BEHAVIOR OF ULTRAFINE GRAINED IRON CHROMIUM ALLOY. Research on stainless steel corrosion resistance continues to grow today. This reality cannot be separated from the needs of stainless steels in various fields, one of which is bio-implant. In this research, the effect of grain size on the corrosion behavior of iron-chromium (Fe-Cr) alloy was investigated. Coarse grain Fe-Cr alloy was first processed with equal channel angular pressing (ECAP) for eight cycles to obtain ultrafine grain structure. The coarse and ultrafine grain samples then were then tested using XRD, SEM-EBSD, and the pitting corrosion properties tested using potentiodynamic polarization method in NaCl 1 M solution. The result of XRD dan SEM-EBSD shows that the initial sample is truly has a coarse grain structure, while ECAP produces an ultrafine grain structure. Corrosion test results showed that the ultrafine grain sample had better pitting corrosion resistance compared to the coarse grain sample. This behavior is related to the rate of passivation that depends on non-equilibrium grain boundaries, which can be easily observed in the ultrafine grain structure. Based on these results, it can be concluded that the ultrafine grain Fe-Cr alloy has a better corrosion resistance compared to the coarse grain.